(untitled) (Global Media Journal - German Edition, 2018)
Various voices assert that the sport-politics nexus that characterized international sport events during the Cold War era is irrelevant in the current age of globalization. This study examines the validity of this argument via a case study of Jewish-Israelis’ fandom tendencies during the 2014 World Cup. A survey conducted during the World Cup games among a representative sample of the Jewish-Israeli population revealed that the Dutch team, whose popularity in Israel has been attributed to the Netherland’s perceived support of Jews during the Holocaust, was the most supported team. The teams most rooted against were Iran, Germany, and Algeria, indicating the potential role of the Holocaust and contemporary Jewish-Islamic relations on fandom tendencies. To better understand the animosity towards the German team, which is surprising in light of current improved Israel-Germany relations and the strength of the German team, we analyzed user comments on Israel’s main online newspaper following the German team’s glorious 7-1 victory against Brazil. The analysis revealed that 51 of the 287 user comments made direct or indirect references to the Holocaust, further highlighting the centrality of nationalism in contemporary sport fandom.